2015
DOI: 10.1364/boe.6.003066
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence depletion properties of insulin–gold nanoclusters

Abstract: Insulin-gold nanoclusters exhibit outstanding biocompatibility, photostability, and fluorescence quantum efficiency. However, they have never been used in superresolution microscopy, which requires nonlinear switching or saturation of fluorescence. Here we examine the fluorescence and stimulated emission depletion properties of gold nanoclusters. Their bleaching rate is very slow, demonstrating superior photostability. Surprisingly, however, the best depletion efficiency is less than 70%, whereas the depletion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Figure shows the absorption and fluorescent spectra of Au NCs. The absorption spectrum shows the characteristic peak at 290 nm of Au NCs . The maximum fluorescence peak of Au NCs appears at 474 nm.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Figure shows the absorption and fluorescent spectra of Au NCs. The absorption spectrum shows the characteristic peak at 290 nm of Au NCs . The maximum fluorescence peak of Au NCs appears at 474 nm.…”
Section: Resultsmentioning
confidence: 98%
“…Many authors have described methods to synthesize stable and highly photostable Au NCs. For examples, multivalent glycosylation of Au NCs was used to promote human dendritic cell targeting, silver‐doped Au NCs showed high photostability and fluorescence, and phosphorothioate DNA and proteins were used to stabilize Au NCs …”
mentioning
confidence: 99%
“…Gold nanoclusters (AuNCs), by definition, are made up of a few to a hundred atoms, being 2–3 nm size, known as quantum clusters or nanoclusters. For such clusters, their small core size can be compared to the Fermi energy (0.8 nm) of the free electrons. , As a result, the clusters show a significant difference in their optical and electronic properties such as quantum-confined, size-tunable electronic transitions from the other two categories. Recently, protein-protected nanoclusters emerged as useful and functional materials possessing interesting properties. , The literature started witnessing reports on the development of green synthesis of AuNCs, where no external reducing and stabilizing agents were used, and instead some proteins and peptides are being used. This includes lysozyme, pepsin, trypsin, transferrin, human serum albumin, bovine serum albumin, insulin, and horse radish peroxidase. An important outcome of all these studies is the near constancy of luminescence, emission wavelength irrespective of core size, and almost complete absence of any distinct features of nanocluster core absorption. , This prompted the nanocluster community to consider the emission as being dominated by an Au + –ligand complex shell as an outer shell of an Au cluster. , While a large number of nuclei of nanoclusters have been analyzed by mass spectrometry, the difficulty associated with obtaining accurate mass analysis of such clusters has limited our understanding. Added to this is the poor electrospray ionization efficiency of protein-protected nanoclusters. , …”
Section: Introductionmentioning
confidence: 95%
“…Glutathione has been extensively used for AuNC synthesis due to the strong affinity of the thiol group to form AuS bond . Cysteine‐containing proteins such as bovine serum albumin, insulin, trypsin, and lysozyme have been also explored for the same purpose. Other studies have also shown that basic amino acids together with tyrosine and tryptophan can contribute to the reduction of the ions to metallic gold .…”
Section: Introductionmentioning
confidence: 99%